Factors affecting the participation of university students in volunteering during the covid-19 pandemic - A study on a sample of Jordanian University students - Al-Nabulsi, Hana Hosni Mohammed (Journal of Humanities & Social Sciences, 2022)
The study aimed to identify the factors that affect the participation of university students in volunteer work during the COVID-19 pandemic, as the study was applied on a sample of Jordanian university students. The researcher adopted the descriptive approach, and the study sample was chosen using simple random sampling, which amounted to (383) male and female students. The study tool was distributed electronically to university students in Jordan. The study has applied descriptive statistics, t-Test, and Multiple Variance Test. The study came out with a set of results, the most important of which are: The factors affecting the participation of university students in voluntary work during the COVID-19 pandemic were generally high. The results showed that volunteering in these circumstances contributes to building new social relationships and achieving a position in society, and that there was a conviction among university students of the importance of their participation in these conditions for groups that need assistance. There was also a high social acceptance of participating in voluntary work during the pandemic and the belief in its importance in mitigating its effects on patients infected with the COVID-19 and their families. The results did not show statistically significant differences at the significance level (α≥0.05) in the level of social, cultural and economic factors that affect the participation of university students in voluntary work due to age, gender and place of residence. The study recommended the necessity of attracting and training university youth by voluntary institutions and bodies to participate in voluntary work in conditions of crises and disasters, and activating electronic volunteering through social networking sites.